Distribution of radioelements in rock-water-air systems from the Caldas Novas hydrothermal complex (GO), Brazil - Lunardi, Marina [UNESP]; Bonotto, Daniel Marcos [UNESP] (Elsevier, 2023)
Radioactivity measurements have been done in rocks and groundwater samples of Caldas Novas Hydrothermal Complex, Goiás State, Central Brazil, aiming to investigate if the rock matrices could be responsible for transferring high levels of radionuclides into the atmosphere and liquid phase. Gamma spectrometry showed that rocks presented low concentrations of uranium (eU = 226Ra), thorium (eTh = 228Th) and 40K as confirmed by laboratorial radon (222Rn) emanation experiments that yielded low values in both, liquid and gas phases. The monitored dissolved radionuclides in waters were 222Rn, 210Pb, 223Ra, 224Ra, 226Ra, 228Ra, 234U, and 238U, whose activity concentration was compared with the guideline reference values established by the World Health Organization (WHO) for drinking water. The results obtained for the committed effective dose (CED), based on a drinking water ingestion rate of 2 L/day throughout a year, did not surpass the WHO reference level of 100 μSv/year.